2022
DOI: 10.1177/21925682221127955
|View full text |Cite
|
Sign up to set email alerts
|

Decompression Alone in the Setting of Adult Degenerative Lumbar Scoliosis and Stenosis: A Systematic Review and Meta-Analysis

Abstract: Study Design Systematic review and meta-analysis. OBJECTIVESSurgical decompression alone for patients with neurogenic leg pain in the setting of degenerative lumbar scoliosis (DLS) and stenosis is commonly performed, however, there is no summary of evidence for outcomes. Methods A systematic search of English language medical literature databases was performed for studies describing outcomes of decompression alone in DLS, defined as Cobb angle >10˚, and 2-year minimum follow-up. Three outcomes were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Hasan et al 2 suggested that MI decompression may lead to favorable outcomes in 45 patients with lumbar spinal canal stenosis and a mean Cobb angle of 15.9°. In addition, in 31 patients with a mean Cobb angle of 17.3°, MI decompression did not show a significant difference in MCID achievement compared to a matched MI short fusion 6 . These findings suggest that MI decompression may be an viable treatment option for patients with a Cobb angle ranging from 10° to 20°.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Hasan et al 2 suggested that MI decompression may lead to favorable outcomes in 45 patients with lumbar spinal canal stenosis and a mean Cobb angle of 15.9°. In addition, in 31 patients with a mean Cobb angle of 17.3°, MI decompression did not show a significant difference in MCID achievement compared to a matched MI short fusion 6 . These findings suggest that MI decompression may be an viable treatment option for patients with a Cobb angle ranging from 10° to 20°.…”
Section: Discussionmentioning
confidence: 80%
“…Early reoperation after decompression is a devastating complication. A systematic review including MI, endoscopic, and open decompression showed that the average reoperation rate was 9.7% 8 . A study comparing full-endoscopic and MI lumbar decompression reported the overall reoperation was 4% within the cohort with a mean Cobb angle of 15.6° 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical management of DLS includes decompression alone, short-segment fusion, and long-segment fusion, but there is conflicting evidence and wide variation in practice between them. 1,[19][20][21] Studies have shown that patients with DLS have similar imaging findings compared to those with simple LSS, including ligamentum flavum hypertrophy, bulging discs, and facet joint degeneration. 22 Since LSS and DLS mainly affect an elderly population with poor surgical tolerance, less invasive decompression alone is an indispensable surgical option for elderly patients with DLS.…”
Section: Discussionmentioning
confidence: 99%